ADMINISTRATIVE SYSTEM OF MONEY ON BORROWING PAWNING KRAMATJATI-EAST JAKARTA - Ade Nunik Pikmiasari; Ir. Susi Wagiyati. MM (Jurnal Sistem Informasi, 2000)
Pawning is a service company that serves the borrowing of money by acceptingcollateral chattels or goods that can be moved place.In this paper the authors try to create a system that can used in the moneylendingbusiness conducted Pawnshop. So that existing work can be done rapidly andaccurately.